2022
DOI: 10.3389/fonc.2022.947899
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric analysis of TRPM6 and TRPM7 from small intestine of omeprazole-induced hypomagnesemic rats

Abstract: Disruption of small intestinal Mg2+ absorption has been reported as the underlying mechanism of proton pump inhibitor-induced hypomagnesemia (PPIH); hence, this study evaluated the expression, localization, phosphorylation, and oxidation of transient receptor potential melastatin 6 (TRPM6) and TRPM7 in the small intestine of rats subjected to PPIH. The expression and localization of cyclin M4 (CNNM4) was also analyzed. We show that, compared to control rats, membrane expression of the TRPM6/7 heterodimer and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Transcellular Mg 2+ absorption occurs through mucosal Mg 2+ uptake by TRPM6 and TRPM7 homodimer channel, both of which were markedly detected in the small intestinal epithelium of human and murine cells[ 10 - 14 ]. In addition, recent mass spectrometric peptide sequence analysis confirmed the expression of TRPM6 and TRPM7 in the duodenum and jejunum[ 15 ]. The channel activities of both homodimers of TRPM6 and of TRPM7 are negatively regulated by physiological Mg·ATP and Mg 2+ levels[ 10 , 16 - 19 ].…”
Section: Mechanism Of Small Intestinal Mg 2+ Absor...mentioning
confidence: 99%
See 4 more Smart Citations
“…Transcellular Mg 2+ absorption occurs through mucosal Mg 2+ uptake by TRPM6 and TRPM7 homodimer channel, both of which were markedly detected in the small intestinal epithelium of human and murine cells[ 10 - 14 ]. In addition, recent mass spectrometric peptide sequence analysis confirmed the expression of TRPM6 and TRPM7 in the duodenum and jejunum[ 15 ]. The channel activities of both homodimers of TRPM6 and of TRPM7 are negatively regulated by physiological Mg·ATP and Mg 2+ levels[ 10 , 16 - 19 ].…”
Section: Mechanism Of Small Intestinal Mg 2+ Absor...mentioning
confidence: 99%
“…The channel activities of both homodimers of TRPM6 and of TRPM7 are negatively regulated by physiological Mg·ATP and Mg 2+ levels[ 10 , 16 - 19 ]. A recent study reported the expression of a heterodimer TRPM6/7 channel in the plasma membrane of duodenal and jejunal epithelium[ 15 ]; therefore, Mg 2+ enters the small intestinal epithelial cells through TRPM6/7, TRMP6, and TRPM7. However, the heterodimer TRPM6/7 channels do not respond to physiological intracellular Mg 2+ and Mg·ATP[ 17 , 19 ]; thus, continuous epithelial Mg 2+ absorption can occur through the TRPM6/7 channel, regardless of intracellular Mg 2+ and concentrations.…”
Section: Mechanism Of Small Intestinal Mg 2+ Absor...mentioning
confidence: 99%
See 3 more Smart Citations